The Cambridge Structural Database in chemical education: analysis of hydrogen‐bonded networks in salts of hexaaqua metal ions with organic counter‐ions. Issue 6 (5th November 2020) - Moret, Massimo
Abstract : This contribution describes a ten‐year experience of teaching a computer‐based inorganic chemistry laboratory course to undergraduates. The course aims to introduce students to structure analysis of simple inorganic molecular solids with a pragmatic approach. Atomic coordinates of molecular crystals and advanced visualization methods available in the Cambridge Structural Database and its associated software allow students to link newly learned crystallographic skills with knowledge acquired in earlier basic courses in inorganic, organic and physical chemistry. Abstract : This paper describes a laboratory course that introduces basic crystallographic data analysis to chemistry students encountering for the first time the world of crystals and crystal structures. The aim of the course is to provide students with direct contact with crystal structures and hands‐on experience in structure analysis. To this end, a set of appropriately simple inorganic molecular structures was selected, consisting of salts of hexaaqua metal ions with organic counter‐ions. By exploiting the crystallographic tools available in the Cambridge Structural Database program Mercury, students learn how to visualize and analyse a set of atomic coordinates. In this way they learn how to extract bonding and structural information concerning intramolecular interactions in both salt components. Intermolecular interactions are next analysed by looking closely at supramolecular motifs and packing patterns generated by hydrogen bonds. This pragmatic approach turned out to be effective and extremely useful for summarizing many chemical concepts learned by students during a bachelor degree course in chemistry. The experience provides at the same time some basic capabilities for properly managing crystal structure analysis.